A methodology for setting up Ggnerator out-of-step protective relays (2006)
In this article a methodology for setting up generator out-of-step protective relay, to be applied in any generator of Colombian Power System is presented. A comparison between settings proposed in research articles and a manufacturer was carried out. The application of the methodology required information as generator direct-axis transient reactance, transformer reactance, power system impedance and critical time for setting up protective relay. The proposed methodology for setting up generator out-of-step protective relay was applied in the Salvajina and Alto Anchicayá power plants, improving the selectivity with new settings approaches.